Drug therapy for allergic rhinitis in children - A. I. Kryukov (Медицинский совет, 2014)
Allergic rhinitis is characterized by increasing incidence and poses a medical and social problem. The article tells about current approaches to the treatment of allergic rhinitis. The use of Nasonex nasal corticosteroid in pediatric practice results in stable clinical improvement.